Atorvastatin accelerates clearance of lipoprotein remnants generated by activated brown fat to further reduce hypercholesterolemia and atherosclerosis - Hoeke, Geerte; Wang, Yanan; van Dam, Andrea D.; Mol, Isabel M.; Gart, Eveline; Klop, Henk G.; van den Berg, Susan M.; Pieterman, Elsbet H.; Princen, Hans M.G.; Groen, Albert K.; Rensen, Patrick C.N.; Berbée, Jimmy F.P.; et al. (Atherosclerosis, 2017)
Activation of brown adipose tissue (BAT) reduces both hyperlipidemia and atherosclerosis by increasing the uptake of triglyceride-derived fatty acids by BAT, accompanied by formation and clearance of lipoprotein remnants. We tested the hypothesis that the hepatic uptake of lipoprotein remnants generated by BAT activation would be accelerated by concomitant statin treatment, thereby further reducing hypercholesterolemia and atherosclerosis. APOE*3-Leiden.CETP mice were fed a Western-type diet and treated without or with the selective β3-adrenergic receptor (AR) agonist CL316,243 that activates BAT, atorvastatin (statin) or both. β3-AR agonism increased energy expenditure as a result of an increased fat oxidation by activated BAT, which was not further enhanced by statin addition. Accordingly, statin treatment neither influenced the increased uptake of triglyceride-derived fatty acids from triglyceride-rich lipoprotein-like particles by BAT nor further lowered plasma triglyceride levels induced by β3-AR agonism. Statin treatment increased the hepatic uptake of the formed cholesterol-enriched remnants generated by β3-AR agonism. Consequently, statin treatment further lowered plasma cholesterol levels. Importantly, statin, in addition to β3-AR agonism, also further reduced the atherosclerotic lesion size as compared to β3-AR agonism alone, without altering lesion severity and composition. Statin treatment accelerates the hepatic uptake of remnants generated by BAT activation, thereby increasing the lipid-lowering and anti-atherogenic effects of BAT activation in an additive fashion. We postulate that, in clinical practice, combining statin treatment with BAT activation is a promising new avenue to combat hyperlipidemia and cardiovascular disease. •Statin treatment accelerates the hepatic clearance of lipoprotein remnants generated by brown adipose tissue activation.•Statin treatment in addition to brown adipose tissue activation further protects from atherosclerosis development.•Brown adipose tissue activation combined with statin therapy is a promising strategy to alleviate cardiovascular diseases.